Pelatihan Menulis Artikel Ilmiah dan Mengirimkannya ke Jurnal Ilmiah - Subekti, Adaninggar Septi (Jurnal Pengabdian UntukMu NegeRI, 2021)
The community service activity was conducted in the form of online training on Zoom and Youtube platforms. The participants were 80 lecturers, teachers, and university students from 28 different institutions. It aimed to facilitate the participants to be able to improve the quality of their scientific articles and to submit their articles to ‘carefully chosen’ journals. It lasted for 100 minutes. There were six important points regarding how the quality of research articles could be maintained and improved. Firstly, the participants should do a lot of reading before writing. Secondly, they should have strong rationales of conducting their studies. Thirdly, they needed to use combination of descriptive and analytical expressions. Fourth, they should write or review only relevant literature in meaty way. Next, they should ensure that all of the in-text citations correspond to the references. Last but not least, they should implement ethical principles in research. Furthermore, regarding how the participants could choose which journal was ‘best’ for their articles, four important points were discussed: choosing a journal which ‘matched’ the quality of the article, choosing a journal with regular publication, adhering to the chosen journal’s template, and asking the journal editors about the duration of the review process.